Acidified Animal Manure Products Combined with a Nitrification Inhibitor Can Serve as a Starter Fertilizer for Maize - Iria Regueiro; Peter Siebert; Jingna Liu; Dorette Müller-Stöver; Lars Stoumann Jensen (Agronomy, 2020)
There is an urgent need for better management practices regarding livestock farm nutrient imbalances and for finding alternatives to the actual use of mineral fertilizers. Acidification of animal manure is a mitigation practice used to reduce ammonia emissions to the atmospheric environment during manure storage and land application. Acidification modifies manure physicochemical characteristics, among which soluble N and P significantly increase. The main objective of this study was to investigate if acidification and the addition of a nitrification inhibitor to manure and placement of the treated manure close to the seed can stimulate maize growth by enhancing nutrient availability, specially P and consequently plant P uptake, at early development stages without the use of mineral N and P as a starter fertilizer. Raw dairy slurry and solid fractions from dairy slurry and digestate from a biogas plant were acidified to pH 5.5 and applied with or without a nitrification inhibitor (DMPP, 3,4-dimethyl pyrazole phosphate) to maize in a pot experiment, where biomass productivity, nutrient uptake and soil P availability were examined. Acidification increased the water-extractable P fraction of all slurry and digestate organic residues (by 20–61% of total P) and consequently plant P uptake from solid fractions of both slurry and digestate compared to the untreated products (by 47–49%). However, higher plant biomass from acidification alone was only achieved for the slurry solid fraction, while the combination of acidification and DMPP also increased plant biomass in the digestate solids treatment (by 49%). We therefore conclude that the combination of acidification and a nitrification inhibitor can increase the starter fertilizer value of slurry and digestate products sufficiently to make them suitable as a maize starter fertilizer.